Folksong across borders:Unveiling the Chinese folksong “Jasmine Flower” through three piano adaptations from Russia, Australia, and Germany - Liang Tao; Jacqueline Pugh-Kitingan; Lee Chie Tsang Isaiah (Faculty of Fine Arts, Srinakharinwirot University, 2024)
The Chinese folksong “Jasmine Flower” is regarded as one of China’s most renowned folksongs. It has several regional variations. Over time, it has been adapted for music played with traditional Chinese musical instruments, as well as for more recent compositions for piano. This article examines three piano adaptations of this iconic Chinese folksong by composers from Russia, Australia, and Germany, highlighting their unique compositional styles and cultural interpretations. It probes deeply into how each composer intricately integrates and applies the folksong within their distinct cultural and historical contexts, particularly emphasising their technical and stylistic approaches. Based on the concept of musical syncretism, the study employs a comprehensive methodology, including in-depth harmonic, textural, and structural analyses, as well as an exploration of the integration of folk elements and innovative compositional techniques. The comparative analysis provides insights into the global dissemination and creative evolution of "Jasmine Flower", significantly contributing to the discourse on cross-cultural musical adaptations and their broader implications. The study also examines how traditional motifs are reinterpreted through modern musical language, balancing preservation and creativity.